Respostas

2013-11-25T11:17:47-02:00
A) 2x+2-6x+15 = 6x-3
-4x-6x= -3 -15-2
-10x = -20 .(-1)
x= 20/10 ---- 2

b) 3x= 2 -5
x= -3/3 ---- -1

c) x-2x+1=23
-x=23-1
-x=22 .(-1)
x= -22
1 2 1
A resposta da Letra A está errada. Refaça-a.
desculpa, me enganei no sinal, vi errado.
Valeu!
2013-11-25T11:30:31-02:00
A) 2 (x + 1) - 3 (2x - 5) = 6x - 3
2x + 2 - 6x + 15 = 6x - 3
2x - 6x - 6x = - 3 - 2 - 15
- 10x = - 20
x = - 20 ÷ (- 10)
x = 2

Tirando a prova:
2 (2 + 1) - 3 (2 * 2 - 5) = 6 * 2 (- 3)
4 + 2 - 3 (4 - 5) = 12 (- 3)
4 + 2 - 12 + 15 = 9
9 = 9


b) 3x + 5 = 2
3x = 2 - 5
3x = - 3
x = - 3 ÷ 3
x = - 1

Tirando a prova:
 3 (- 1) + 5 = 
- 3 + 5 = 
2

h) x - (2x - 1) = 23
x - 2x + 1 = 23
- x + 1 = 23
- x = 23 - 1
- x = 22
x = - 22

Tirando a prova:
- 22 - (2 (- 22) - 1) =
- 22 - (- 44 - 1) =
- 22 - (- 45) =
- 22 + 45 =
23